Measurements of turbulence generated by oscillating grid - Cheng, Nian-Sheng (2012)
Turbulence generated by a vertically oscillating grid in a water tank was investigated using the digital particle image velocimetry technique. The statistical turbulence characteristics computed based on the experimental data agree well with the two main findings reported in the literature: (1) The turbulence decays following the power law; and (2) the integral length scale increases linearly with the distance from the grid. In addition, the flow structure near the grid was observed in detail with the advantage of the planar measurements. It was found that the velocity fluctuations in the region near the grid vary depending on the grid geometry. The fluctuations immediately over the bar position are significantly different from those over the grid openings. Turbulence with the highest intensity occurs above the intersection of the square bars that constitute the grid. The results imply that shear flow clearly exists near the grid and homogeneity of the turbulence can only be achieved at a distance from the grid greater than about three mesh sizes. In addition, it was found that at least 400 vector maps should be taken to ensure the accuracy of the measured velocity fluctuations.